1991
DOI: 10.1007/bf00406193
|View full text |Cite
|
Sign up to set email alerts
|

A study of the prevalence of respiratory morbidity among agate workers

Abstract: A random sample of 342 workers engaged in chipping and grinding of agate stones were surveyed in a cross-sectional study to assess the prevalence of respiratory morbidity in the agate industry. The findings were compared with those obtained in controls. The study showed a significantly higher prevalence of lung diseases among agate workers than among controls (63.4% vs 35.5%, P less than 0.001). The respiratory morbidity in agate workers and controls was maximal in the group aged 31+ years (83.3% and 42.2%, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 6 publications
0
22
3
Order By: Relevance
“…The carving process in our country differs from that described on the few reports about silicosis among lapidary workers [Ng et al, 1985[Ng et al, , 1987Chapman and Tracey, 1989;Rastogi et al, 1991;White et al, 1991;Jiang et al, 2001;Yingratanasuk et al, 2002].…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The carving process in our country differs from that described on the few reports about silicosis among lapidary workers [Ng et al, 1985[Ng et al, , 1987Chapman and Tracey, 1989;Rastogi et al, 1991;White et al, 1991;Jiang et al, 2001;Yingratanasuk et al, 2002].…”
Section: Discussioncontrasting
confidence: 75%
“…As previously described by Ng et al [1985] and White et al [1991], we noticed that most of the stone sculptors work at home, in little workshops, without adequate engineering control. The variety of minerals used by the artisans also makes our study different from others that report the use of only one type of stone, such as jade [Ng et al, 1985], agate [Rastogi et al, 1991;Jiang et al, 2001], and tiger's eye [White et al, 1991]. However, most of the minerals used in Petrópolis are varieties of quartz.…”
Section: Discussioncontrasting
confidence: 54%
“…However, Rastogi et al [1991] reported a silicosis prevalence of 18.4% in agate grinders and chippers in India, and the silica content was 82%. In Chinese, there was no previous report on agate workers.…”
Section: Discussionmentioning
confidence: 91%
“…Long-term exposure leads to development of silicosis and increased susceptibility to tuberculosis 5) and to a higher risk of developing lung cancer 6) . Previous reports 4,7) and recent studies 8,9) continue to report high incidences of silicosis among agate workers. Agate workers are usually involved in various processes, including stone cutting, stone grinding, and polishing work on agate stones for ornamental and jewellery purposes 10) .…”
mentioning
confidence: 86%